ANALISIS FRONT SALINITAS BERDASARKAN MUSIM DI PERAIRAN PANTAI BARAT SUMATERA [Analysis of Salinity Front by Season in the Coastal West of Sumatra] - Supiyati, Supiyati; Suwarsono, Suwarsono; Astuti, Nissa (BERITA BIOLOGI, 2016)
Technology of the marine sciences, especially the potential  resources of fish can be evalute from front area identification. The aim of this research is to identify front salinity area based on seasonal variation in the west coastal of Sumatra. The method involved modeling by ODV  (Ocean Data View), Fortran, Transform, and Matlab software. We used salinity data what obtained from NOAA (National Oceanic and Atmospheric Administration). The result showed that vertically, front areas in coastal West of Sumatera for all off season was in depth of ± 41.6 meters, 83.2 meters and 124.8 meters. In the North West Monsoon, salinity front area was around of the Nias, Simeulue, Northwest and southeast  of Enggano islands. On the first of transition period was in West of Simeulue, southeast of Nias, and East Enggano Islands. In the South East Monsoon was in the Northeast of Simeulue, the East of Mentawai, Southeast and Northwest of Enggano Islands. On the second transition period was in the Eastern of Nias and Mentawai Islands. Salinity changes of fourth monsoons on this front area is ± 0,5 psu.